Factors associated with the alteration of baseline glycemia in the first posthospitalization checkup in patients with type 2 diabetes mellitus - Alva Cabrera, Ana Denisse (2018)
Objective: To analyze the factors associated with the alteration of baseline glycemia in the first post-hospitalization checkup in patients with type 2 diabetes mellitus (T2DM). Materials and methods: A retrospective observational case-control study was performed in a 1:1 ratio. One hundred (100) medical records of patients of both genders and over 18 years of age with T2DM who had a medical checkup within the first 3 months after hospitalization were analyzed. Cases were defined as those with high baseline glycemia (> 130 mg/dL) and controls were defined as those who had normal glycemic levels (≤ 130 mg/dL). Mean and percentages were estimated using the chi-square test and binary logistic regression. Results: Elevated glycemic levels at admission (OR: 2.7, p <0.05), elevated glycemic levels at discharge (OR: 3.7, p <0.005), HbA1c ≥ 9 % during hospitalization (OR: 2.9, p <0.05), high levels of triglycerides (OR: 2.6, p <0.05), and failure to comply with prescribed treatment (OR: 2.15, p <0.005) were associated with high baseline glycemia in the first posthospitalization checkup. Conclusions: High levels of triglycerides and non-compliance with indications are risk factors associated with poor glycemic control at the first outpatient visit after hospitalization.